Addressing the teacher shortage in Australia: what do the Initial Teacher Education (ITE) completion data tell us? - Loan Dao; Jeanne Allen; Darren Pullen; Scott Cowie (Springer, 2024)
Abstract With projections from the Australian federal government indicating an impending exacerbation of the teacher shortage by 2025, it is timely to explore potential approaches that could help mitigate this imminent national crisis. In teaching, there is an historical tendency for the teaching profession to attract more women than men and this study therefore aims to analyse trends in female completion rates of Initial Teacher Education (ITE) degrees. The study objective was to identify the specific teaching degree levels (undergraduate and postgraduate) and modes of attendance that are most likely to continue attracting women to pursue careers in teaching. This research relies on non-identifiable open access data obtained from Australian ITE providers between 2001 and 2021, which have been collected by the Australian Government Department of Education, Skills and Employment. The study findings reveal an upward trend in female completions of ITE programs offered through external and multimodal study modes, while the internal mode of attendance show a decline. These findings hold significant implications for policy and practice, suggesting the need to enhance the accessibility of external and multimodal ITE degrees for women.